2009
DOI: 10.1021/cg9004032
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Brookite TiO2 Flowers: Synthesis, Characterization, and Dielectric Performance

Abstract: High-quality brookite flowers were fabricated via a facile solution chemistry technique. The synthetic conditions to the flower-like brookite were monitored by a series of time-resolved experiments and further optimized by adjusting the concentrations of the Na + and OHspecies involved in the reaction system. Careful sample characterizations by the combined techniques of X-ray diffraction, Raman, high resolution transmission electron microscopy, X-ray photoelectron spectroscopy, and electron paramagnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(166 citation statements)
references
References 60 publications
8
158
0
Order By: Relevance
“…On the other hand, an unusual single (121) peak was found for a film containing neither anatase nor rutile obtained by a modified sol-gel method [4]. Hu et al [5] used one characteristic peak of anatase at 2θ = 62.57°, which does not overlap with any diffraction peak of brookite, to ascertain the existence of anatase. According to Bokhimi and Pedraza [6] the only way to prove that the samples are single brookite phase is to run their XRD patterns with a good statistic to refine the crystalline structure of brookite in order to demonstrate that the modeling of only this phase is enough to reproduce the experimental diffraction pattern.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, an unusual single (121) peak was found for a film containing neither anatase nor rutile obtained by a modified sol-gel method [4]. Hu et al [5] used one characteristic peak of anatase at 2θ = 62.57°, which does not overlap with any diffraction peak of brookite, to ascertain the existence of anatase. According to Bokhimi and Pedraza [6] the only way to prove that the samples are single brookite phase is to run their XRD patterns with a good statistic to refine the crystalline structure of brookite in order to demonstrate that the modeling of only this phase is enough to reproduce the experimental diffraction pattern.…”
Section: Figurementioning
confidence: 99%
“…High quality brookite flowers were obtained by Hu et al [5] by hydrothermal treatment at 220 °C for 48 h of a suspension containing TiOSO 4 and NaOH at pH 12.5. Time-resolved experiments revealed that layered titanate transformed into spindle-like brookite nanoparticles that aggregated together to yield the flower morphology.…”
Section: Brookite Nanomaterialsmentioning
confidence: 99%
“…Among these polymorphs, rutile and anatase have been widely studied. Brookite is rarely studied due to its complicated structure and difficulties in sample preparation (Hu et al 2009). These three phases can be commonly described as constituted by arrangements of the same building block-Ti-O 6 octahedron in which Ti atom is surrounded by six oxygen atoms situated at the corners of a distorted octahedron.…”
Section: Introductionmentioning
confidence: 99%
“…This variation indicates that the least negative synthesis potential is the most favorable condition for brookite polymorph, in accordance with XRD analysis. Figure 6d shows the positions of anatase and brookite fitted modes for all TT temperatures as function of the electrosynthesis potential, as well as the calculated position of these modes (dashed lines) [6,14,15]. There is no significant shift of the position of B mode for 400 and 600°C.…”
Section: Crystalline Structurementioning
confidence: 96%